The Effectiveness of Commissioners Board Size And Audit Commitee Size on Risk Disclosure - Yubiharto Yubiharto; Walid Rudianti (Universitas Batanghari, 2021)
The purpose of this study is to analyse the effectiveness of the Commissioners Board size Audit Committee size on risk disclosure (empirical study on coal-mining sub-sector under mining sector companies listed on Indonesian Stock Exchange during the period of 2016-2018). The samples for this study are 19 companies under coal-mining sub-sector listed in Indonesian Stock Exchange during the period of 2016-2018. The methodology used in this study is multiple linear regression with data panel approach. Commissioners Board size has a positive and significant effect on risk disclosure in the companies under mining sector and coal-mining sub sector listed in IDX during the period of 2016-2018. Meanwhile, audit committee size has a negative and significant effect on risk disclosure in the companies under mining sector and coal-mining sub sector listed in IDX during the period of 2016-2018. It is advisable for investors and prospective investors to consider Commissioners Board size and Audit Committee size.